PELATIHAN INFORMASI DAN KOMUNIKASI TEKNOLOGI - Weko Susanto; Nur Samsul Huda; Yuliarman Saragih (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Information and Communication Technology (ICT) currently affects every aspect of human life. They play an important role in the workplace, business, education and entertainment. In addition, many recognize ICT as a catalyst for change. Changes in working conditions, handling and exchange of information, teaching methods, learning approaches, scientific research, access to information and communication technology. In this digital era, the use of ICT in the classroom is essential to provide opportunities for students to learn and apply the skills needed for the 21st century. ICT is important for teachers in strengthening education and learning as well as playing a role as creators of the educational environment. ICTs help teachers present their teachings in an engaging and educational way to students at all levels of the educational program. Teaching in India today makes training programs using ICT terminology useful and interesting. Information and Communication Technology (ICT), represented by the Internet and interactive multimedia, is clearly an important focus for future education and needs to be effectively integrated into formal education and learning, especially in teacher education institutions.